Pengaruh Sektor Industri, Komersial dan Pendapatan Terhadap Konsumsi Energi Listrik Bersumber Fosil di Indonesia - Alfajar, Ridho; Suparta, I Wayan; Moniyana Putri, Resha (CV. ITTC INDONESIA, 2025)
Fossil-based electricity consumption in Indonesia has continued to rise in recent years, driven by accelerated economic growth, expansion of the industrial and commercial sectors, and increasing household income levels. This strong reliance on fossil energy has contributed to higher carbon emissions and heightened vulnerability to supply instability. Therefore, understanding the key determinants of electricity consumption is essential for supporting Indonesia’s national energy transition agenda toward a more sustainable energy system. This study aims to examine the influence of the industrial sector, commercial sector, and income level on fossil-based electricity consumption in Indonesia during the 2019–2023 period. The study employs panel data analysis using the Random Effect Model (REM). This model was selected through the Chow test, Hausman test, and Lagrange Multiplier test, all of which indicated that REM provides the most efficient estimation for accommodating variations across provinces and years. The data were obtained from Statistics Indonesia (BPS), PT PLN, and other relevant official publications. The results reveal that the industrial sector, commercial sector, and income level all exert a positive and significant effect on electricity consumption. Industrial and commercial activities represent the primary drivers of rising national electricity demand, while increases in per capita income contribute to greater household electricity use. The coefficient of determination (R² = 0.7201) demonstrates that the model has strong explanatory power in describing interprovincial variations in fossil-based electricity consumption. These findings highlight Indonesia’s continued dependence on fossil energy, underscoring the need to accelerate renewable energy adoption and improve energy efficiencyas strategic steps to support the national energy transition.